Structural characterization of drug-like compounds by ion mobility mass spectrometry: comparison of theoretical and experimentally derived nitrogen collision cross sections. - Campuzano, I; Bush, M; Robinson, C; Beaumont, C; Richardson, K; Kim, H; Kim, H (2012)
We present the use of drug-like molecules as a traveling wave (T-wave) ion mobility (IM) calibration sample set, covering the m/z range of 122.1-609.3, the nitrogen collision cross-section (Ω(N(2))) range of 124.5-254.3 Å(2) and the helium collision cross-section (Ω(He)) range of 63.0-178.8 Å(2). Absolute Ω(N(2)) and Ω(He) values for the drug-like calibrants and two diastereomers were measured using a drift-tube instrument with radio frequency (RF) ion confinement. T-wave drift-times for the protonated diastereomers betamethasone and dexamethasone are reproducibly different. Calibration of these drift-times yields T-wave Ω(N(2)) values of 189.4 and 190.4 Å(2), respectively. These results demonstrate the ability of T-wave IM spectrometry to differentiate diastereomers differing in Ω(N(2)) value by only 1 Å(2), even though the resolution of these IM experiments were ∼40 (Ω/ΔΩ). Demonstrated through density functional theory optimized geometries and ionic electrostatic surface potential analysis, the small but measurable mobility difference between the two diastereomers is mainly due to short-range van der Waals interactions with the neutral buffer gas and not long-range charge-induced dipole interactions. The experimental RF-confining drift-tube and T-wave Ω(N(2)) values were also evaluated using a nitrogen based trajectory method, optimized for T-wave operating temperature and pressures, incorporating additional scaling factors to the Lennard-Jones potentials. Experimental Ω(He) values were also compared to the original and optimized helium based trajectory methods.